ЗАҲИРИДДИН МУҲАММЕД БАБУР ДӨРЕТИЎШИЛИГИ ҲӘМ ТҮРКМЕН ӘДЕБИЯТЫ - Керуенов, Т. (FAN va JAMIYAT, 2018)
The article deals with the works of the Uzbek poet Zakhretdin Mukhammad Bobur and his influence on Turkmenian literature.